PERAN MASYARAKAT DALAM PERKEMBANGAN MENTAL ANAK DI ERA TEKNOLOGI - Putri Dwi Hariyanto; Hanif Krisna Adhiansyah; Alivia Khoirunnisa; Adinda Dwi Putri Lestari; Rizka Elan Fadilah; I Ketut Mahardika; Firdha Yusmar (FKIP e-PROCEEDING, 2022)
Information technology brings significant changes in the technology era. This development is very useful to support various human activities. Almost all activities have used technology. Changes in technology make activities faster and more efficient. In the world of education, almost all have used technology. Educational technology in general can be regarded as the application of technology in educational activities. Technological changes make changes, especially to children's mentality. This change certainly has its own impact on the mentality of children. The mental readiness of children for technological development must be considered properly. Technological developments can change attitudes in children, which results in less good for the child's future. Children's mental development can be known through the nature and character of each in a different development process. This study aims to provide information about the positive and negative impacts of technological developments, especially on children's mental health. This research was carried out using the literature study method. The conclusion of this study is that the role of the community in monitoring child development is very necessary, so that mental development in children can run well, so that prevention can be done that is helpful for the child's development process.